2018
DOI: 10.3389/fncel.2018.00215
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Responses to Pro-inflammatory Stimuli (LPS, IFNγ+TNFα) and Reprogramming by Resolving Cytokines (IL-4, IL-10)

Abstract: Microglia respond to CNS injuries and diseases with complex reactions, often called “activation.” A pro-inflammatory phenotype (also called classical or M1 activation) lies at one extreme of the reactivity spectrum. There were several motivations for this study. First, bacterial endotoxin (lipopolysaccharide, LPS) is the most commonly used pro-inflammatory stimulus for microglia, both in vitro and in vivo; however, pro-inflammatory cytokines (e.g., IFNγ, TNFα) rather than LPS will be encountered with sterile C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
211
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(247 citation statements)
references
References 119 publications
15
211
0
1
Order By: Relevance
“…Intriguingly, Ym1 was significantly upregulated with M1 stimulation alone. In fact, a previous study has shown that LPS exposure increased the expression of Ym1 in rat primary microglia 24 h after stimulation, suggesting that Ym1 is not a typical M2 marker for these cells [45]. In addition, combined IL-13 and M1 stimulation increased MerTK and Gal3 levels, a receptor and its ligand known to be associated with the phagocytic activity of microglial cells [30,31].…”
Section: Discussionmentioning
confidence: 87%
“…Intriguingly, Ym1 was significantly upregulated with M1 stimulation alone. In fact, a previous study has shown that LPS exposure increased the expression of Ym1 in rat primary microglia 24 h after stimulation, suggesting that Ym1 is not a typical M2 marker for these cells [45]. In addition, combined IL-13 and M1 stimulation increased MerTK and Gal3 levels, a receptor and its ligand known to be associated with the phagocytic activity of microglial cells [30,31].…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, the intracellular nitric oxide (NO) release is also involved in the signal transduction of inflammatory responses (Sagar et al, ). It is important to inhibit the over‐production of NO in response to inflammatory stimuli, which can induce proinflammatory responses in inflammatory disorders (Lively & Schlichter, ). Compared to the blank, the NO level was significantly increased in LPS‐stimulated RAW264.7 macrophage cells ( p < .01) (Figure c), and the pretreatment of gypenosides inhibited the NO production in a dose‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the intracellular nitric oxide (NO) release is also involved in the signal transduction of inflammatory responses (Sagar et al, 2017). It is important to inhibit the over-production of NO in response to inflammatory stimuli, which can induce proinflammatory responses in inflammatory disorders (Lively & Schlichter, 2018).…”
Section: Effect Of Gypenosides On the Secretion Of Proinflammatorymentioning
confidence: 99%
“…The present study was performed to reveal to what extent glycine affected the viability, activation state and secretory activity of microglial cells during inflammation. BV-2 cells were stressed with a combination of LPS and IFN-γ over 24 h. LPS is the most common pro-inflammatory stimulus and causes inflammatory reactions in primary microglia and BV-2 cells [17,18], and IFN-γ is released during CNS injury [18][19][20]. Approximately 90% of the genes induced in BV-2 cells after LPS exposure were also found in primary microglia and showed similar reaction patterns [21], which warrants this cell line as a suitable experimental model.…”
Section: Discussionmentioning
confidence: 99%